STRATEGI PENGEMBANGAN USAHA TERNAK AYAM RAS PETELUR DI CV. MAJU BERSAMA FARM MELALUI ANALISIS SWOT DAN QSPM - Hidayat, Taufiq; Danapriatna, Nana; Kamilah, Ahya (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2024)
CV Maju Bersama Farm is one of the laying hen farms that is still in the development stage. Various obstacles from both the internal and external environment of the company surround the running of the business. The purpose of this study is to determine: a) internal and external factors that affect the business, b) business position, c) business development strategies and d) priority business development strategies that can be applied for business development. This study was studied using a qualitative descriptive approach. Data analysis in this study includes the IFE and EFE matrices, IE matrices, SWOT matrices, and QSPM matrices. The research data comes from primary and secondary data. Based on the IFE matrix, it is known that the main strength is that the eggs produced have good quality and the main weakness is that production has not met consumer demand. In the EFE matrix, the main opportunity is that market demand for broiler eggs is quite high and the main threat is fluctuations in the price of feed, medicines, and egg prices. The results of the IE matrix show that CV Maju Bersama Farm is in cell I which directs the growth and development strategy. There are six alternative strategies from the SWOT analysis with the main priority strategy being to increase chicken capacity by utilizing available land in order to meet demand.